MANAJEMEN PENINGKATAN AKHLAK MULIA DI SEKOLAH BERBASIS ISLAM - Ririn Nursanti (Institut Agama Islam Negeri Purwokerto, 2014)
Moral crisis phenomena experienced by our students are at alarming level. Educational institutions come as enlighten bodies to anticipate such situations by optimizing each part of learning environments in order to build studentâ€™s characters comprehensively. There is a need of breakthrough innovation of reliable management programs so that the students can get their ready-to-life skills to face the nowadays phenomena as well as the future ones. This article will elaborate the descriptive study of how to manage noble-character improvements particularly in Islamic School. The study shows that the management of improving noble character in the Islamic School must be performed through the following stagess: planning, organizing, mobilizing, and monitoring. The strategy that can be chosen to implement character-educations management in Islamic schools are as follows: 1) Achieve teachers' commitment to the implementation of moral education (teacher component), 2) Integrate character education into the curriculum (curriculum component), 3) Creating a financial plan in favour of the implementation of moral education (financing component), and 4) Designing and creating a school culture based on moral education (management component).Â Krisis akhlak yang melanda peserta didik saat ini menjadi fenomena sosial yang cukup memprihatinkan. Lembaga pendidikan sebagai pengemban fungsi konservatif/penyadaran diharapkan dapat memanfaatkan dan memberdayakan semua lingkungan belajar untuk melaksanakan proses pendidikan akhlak secara optimal. Sehingga diperlukan upaya inovatif untuk mengembangkan pendidikan akhlak tersebut agar mampu menghasilkan peserta didik yang ready for life di era globalisasi dengan manajemen yang handal. Penelitian ini bertujuan untuk menjelaskan manajemen peningkatan akhlak mulia khususnya di sekolah Islam. Hasil penelitian menunjukkan bahwa manajemen peningkatan akhlak mulia di sekolah harus melalui tahapan perencanaan, pengorganisasian, penggerakkan, dan pengawasan. Adapun strategi yang dapat dilakukan dalam mengimplementasikan manajemen pendidikan akhlak di sekolah Islam adalah dengan melalui: 1) Mewujudkan komitmen guru dalam pelaksanaan pendidikan akhlak (komponen guru), 2) Mengintegrasikan pendidikan akhlak ke dalam kurikulum (komponen kurikulum), 3) Membuat rencana pembiayaan yang berpihak pada pelaksanaan pendidikan akhlak (komponen pembiayaan), dan 4) Mendesain dan menciptakan budaya sekolah berbasis pendidikan akhlak (komponen pengelolaan.